Preliminary SAR on indole-3-carbinol and related fragments reveals a novel anticancer lead compound against resistant glioblastoma cells. Issue 7 (1st April 2017) - Sherer, Christopher; Tolaymat, Ibrahim; Rowther, Farzana; Warr, Tracy; Snape, Timothy J.
Graphical abstract: Abstract: The prognosis for glioblastoma patients is, at best, poor, with the median time of survival after diagnosis measured in months. As such, there is much need for the rapid development of potent and novel treatments. Herein, we report our preliminary findings on the SAR of a series of indole-3-carbinol and related fragments and reveal a potent lead with low micromolar activity against a particularly resistant glioblastoma cell culture, providing a new platform for future development of a new therapy in this area.